Statewide Professional Development Conference - Paul V. Bredeson; Jay Paredes Scribner (Arizona State University, 2000)
In an environment increasingly skeptical of the effectiveness of large-scale professional development activities, this study examines K-12 educators' reasons for participating and beliefs in the utility in a large-scale professional development conference. Pre- and post-conference surveys revealed that while financial support played a significant role in educators' ability to participate, they were drawn to the conference by the promise to learn substantive issues related to, in this case, performance assessmentwhat it means, how to implement it, and how to address community concerns. In spite of the conference's utility as a means to increase awareness of critical issues and to facilitate formal and informal learning, well conceived linkages to transfer new knowledge to the school and classroom were lacking.